The participants selection system for Al-Qur'an tahfidz competition using the Simple Additive Weighting method - Hidayah, Nurul; Santi, Indyah Hartami; Primasari, Yusniarsi (Journal of Information System and Application Development, 2024)
The Hidayatullah Foundation is an Al-Qur'an-based school that has a tahfidz Al-Qur'an program that is taught every day to students. By holding the Tahfidz competition, it is hoped that it can provide motivation to students to increase their enthusiasm for memorizing the Al-Qur'an. However, so far the selection system that has been carried out by the school still uses manual methods by estimating students who are deemed capable without thorough calculations being carried out. So the selection of students is felt to be unfair and there is no opportunity for other students to take part in the competition. The application of the decision support system uses the Simple Additive Weighting (SAW) method with the results of the grades and ranking of the best students in the Tahfidz program which is carried out through a system calculation process with the first rank with alternative A10 getting a result of 0.996342132 named Alicia from class 3. The test results using the confusion matrix show the value accuracy of 96.9% which indicates a high level of accuracy. It was concluded that the SAW method could be used to select students to take part in competitions.